Effect of Sowing Times on the Yield and Yield Attributes of Rice (Oryza sativa L.) Varieties - JAGTAP, D. N.; CHAVAN, V. G.; MAHADKAR, U. V.; CHAVAN, S. A. (Journal of the Indian Society of Coastal Agricultural Research, 2016)
A field experiment was conducted during Kharif season of 2015-16 to study the effect of sowing times on the growth and yield of different rice varieties. The experiment was laid out in split plot design with three replications. The main plot treatments were three sowing times, viz., 23rd meteorological week, 24th meteorological week and 25th meteorological week. The subplot treatments comprised nine rice varieties viz., Karjat-5, Karjat-7, Ratnagiri-24, Karjat-2, Palghar-1, Karjat-3, Swarna, Sahyadri-4 and Jaya. Thus there were 27 treatment combinations. From the present investigation it is concluded that Kharif rice in Konkan can be sown during 23rd meteorological week with hybrid Sahyadri-4 followed by conventional variety Jaya and Swarna, so as to obtain higher yield and economic returns.